FILSAFAT ILMU DAN PERANANNYA TERHADAP KEMAJUAN PERKEMBANGAN ILMU PENGETAHUAN - Intan Yulia Putri; Muhammad Nurwahidin; Sudjarwo Sudjarwo (Bajang Institute, 2022)
Philosophy is one of the many sciences that examines how to find answers, truth and nature in seeking the truth of various things. Philosophy has several aspects, including parts of philosophy, epistemology, and axiology. Ontology itself in philosophy relates to the benefits and for what role science has a role in human life. Science is a tool and a way to seek the truth so that humans can easily experience development and progress towards a better direction. Because every human being requires information to have the option to adjust, science is a provision that assumes a vital part in human existence the surrounding environment.